The Effect of the Role-Playing Learning Model Assisted by Educational Videos on Learning Outcomes regarding the "I Am a Righteous Child" (Aku Anak Saleh) Topic for Grade IV-B Students at SDN 005 Samarinda Seberang in the 2025/2026 Academic Year - Bidadari Jannatul Ma’wa; Taufik Hidayat; Makmun Makmun; Tri Wahyuningsih; Laras Pratiwi (al-Afkar, Journal For Islamic Studies, 2026)
Students’ learning outcomes in Islamic Education at SDN 005 Samarinda Seberang are relatively low due to the dominance of conventional teaching methods that limit student engagement. This study aims to examine the effect of the Role Playing learning model assisted by educational videos on the learning outcomes of fourth-grade students. The research employed a quantitative approach using a One Group Pretest-Posttest design involving 28 students. Data were collected through multiple-choice tests and analyzed using a paired sample t-test. The results showed that the mean pretest score of 55.71 increased to 81.25 in the posttest, with a significance value of 0.000 < 0.05, indicating a significant effect. These findings demonstrate that the implementation of the Role Playing model assisted by educational videos effectively improves students’ learning outcomes. Therefore, this model is recommended to create a more active, engaging, and meaningful learning process.